2016
DOI: 10.1186/s12862-016-0661-9
|View full text |Cite
|
Sign up to set email alerts
|

Breeding system, shell size and age at sexual maturity affect sperm length in stylommatophoran gastropods

Abstract: Background: Sperm size and quality are key factors for fertilization success. There is increasing empirical evidence demonstrating that sperm form and function are influenced by selective pressures. Theoretical models predict that sperm competition could favour the evolution of longer sperm. In hermaphrodites, self-fertilizing species are expected to have shorter sperm than cross-fertilizing species, which use sperm stored from several mating partners for the fertilization of their eggs and thus are exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Subramoniam, 18 reported that, most of the hermaphroditic animals undergoes cross fertilization to acquire genetic diversity. Preponderantly cross-fertilization was found in many gastropodan species 19 . Nakadera and Koene 20 reported that internal fertilization was mostly found in gastropods but some sea, freshwater and land snail gastropods were also undergo for external fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…Subramoniam, 18 reported that, most of the hermaphroditic animals undergoes cross fertilization to acquire genetic diversity. Preponderantly cross-fertilization was found in many gastropodan species 19 . Nakadera and Koene 20 reported that internal fertilization was mostly found in gastropods but some sea, freshwater and land snail gastropods were also undergo for external fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…DNA sequences from a further 86 representatives of the Orthalicoidea were obtained Gen-Bank stemming from the works of [6,7], as well as [9][10][11][13][14][15][16][17] (Table 2). Representatives of Achatinidae and Strophocheilidae were included as outgroup to root the trees (Tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…Female polyandry is predicted to promote not only the evolution of larger testes and thereby ejaculate quantities, but also higher-quality (e.g., longer tails and faster) sperm (Fitzpatrick et al 2009;Schmera et al 2016).…”
Section: Outer Dense Fiber Proteinmentioning
confidence: 99%